2022
DOI: 10.3390/math10142371
|View full text |Cite
|
Sign up to set email alerts
|

Social Sustainability and Resilience in Supply Chains of Latin America on COVID-19 Times: Classification Using Evolutionary Fuzzy Knowledge

Abstract: The number of research papers interested in studying the social dimension of supply chain sustainability and resilience is increasing in the literature. However, the social dimension is complex, with several uncertainty variables that cannot be expressed with a traditional Boolean logic of totally true or false. To cope with uncertainty, Fuzzy Logic allows the development of models to obtain crisp values from the concept of fuzzy linguistic variables. Using the Structural Equation Model by Partial Least Square… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…The coronavirus disease 2019 (COVID-19) outbreak brought the world the need for non-pharmaceutical sanitary measures and mobility interventions such as social isolation with physical distancing, which made work from home a reality while waiting for vaccines to ensure a safe return to normal activities [ 6 , 7 ]. Managers (whether in the public or private spheres) needed to learn to manage uncertainties to keep organizational activities running while dealing with different risks [ 8 ], especially at the personnel level.…”
Section: Introductionmentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID-19) outbreak brought the world the need for non-pharmaceutical sanitary measures and mobility interventions such as social isolation with physical distancing, which made work from home a reality while waiting for vaccines to ensure a safe return to normal activities [ 6 , 7 ]. Managers (whether in the public or private spheres) needed to learn to manage uncertainties to keep organizational activities running while dealing with different risks [ 8 ], especially at the personnel level.…”
Section: Introductionmentioning
confidence: 99%
“…In emerging Latin America, the study by Rodríguez et al [56] linked social aspects with value creation in industrial cooperatives in Ecuador, Peru, Guatemala, and El Salvador. In Latin America, Reyna-Castillo et al [31] confirmed measures of social sustainability linked to corporate commitment in Mexico and Colombia, subsequently associating it with the resilience of the supply chain of suppliers in Mexico and Chile within the context of the pandemic [36].…”
Section: Social Sustainability As a Corporate Capabilitymentioning
confidence: 98%
“…Inclusion and diversity issues are also essential factors in corporate social sustainability [33,62]. Recently, in Latin economies, Reyna-Castillo et al [36] found the dimensions of Health and Safety, Labor Rights, Social Responsibility, and Inclusion relevant in the supply chain. Marshall et al [63] highlighted the importance of the Social Sustainability Orientation variable, which can be described as the cognitive (not necessarily practical) conviction about caring for social aspects within the firm.…”
Section: Social Sustainability Orientation and Social Sustainability ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Attempts have been made to address this aspect of the freight transport sustainability (Awaysheh & Klassen, 2010;Morali & Searcy 2013;Lo et al, 2021), yet, it is unclear which key conceptions are applied in the field and how they connect to one another. Social dimension is mentioned in research (Ahi & Searcy, 2013;Ashby et al, 2012), although this idea is not the focus of their investigation (Reyna et al, 2022). Also, research demonstrates a lack of attention to social aspect of sustainable freight transport through use of empirical models (Mani, et al, 2016;El Amrani et al, 2021).…”
Section: Freight Transport's Social Sustainabilitymentioning
confidence: 99%